2010
DOI: 10.1016/j.ejvs.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Ultrasonography-Aided Early Diagnosis of Venous Thromboembolism after Total Knee Arthroplasty

Abstract: Application of a scoring system based on the detection of both DVT and HITS may be an effective and efficient method of screening for PE after knee arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Asymptomatic DVT often develops after THA or TKA that have been shown to be a high risk for the development of DVT [3,5], even with the use of currently recommended mechanical and pharmacological prophylaxis. The incidences of DVT after THA (22%) and TKA (63%) in the present study are comparable with the results of recent studies showing incidences of 20-34% in patients who underwent THA [5,6] and incidences of 48-61% in patients who underwent TKA [5][6][7]. Collectively, the findings indicate that more accurate risk stratification and improved prophylaxis are necessary for prevention of DVT in patients undergoing major orthopedic surgery.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Asymptomatic DVT often develops after THA or TKA that have been shown to be a high risk for the development of DVT [3,5], even with the use of currently recommended mechanical and pharmacological prophylaxis. The incidences of DVT after THA (22%) and TKA (63%) in the present study are comparable with the results of recent studies showing incidences of 20-34% in patients who underwent THA [5,6] and incidences of 48-61% in patients who underwent TKA [5][6][7]. Collectively, the findings indicate that more accurate risk stratification and improved prophylaxis are necessary for prevention of DVT in patients undergoing major orthopedic surgery.…”
Section: Discussionsupporting
confidence: 88%
“…Venous thromboembolism (VTE), including pulmonary embolism (PE) and both symptomatic and asymptomatic deep vein thrombosis (DVT), develops after total hip arthroplasty (THA) or total knee arthroplasty (TKA), despite the use of current recommended prophylaxis [1][2][3][4][5][6][7]. Thus, accurate risk stratification is needed to improve prophylactic strategies after major orthopedic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Regular Doppler screening during postoperative period is not recommended. But, prophylaxis is advocated as it is recognized that asymptomatic DVT can produce a fatal PE [6] (Figure 2). Methods of DVT Prophylaxis after Total Knee Arthroplasty http://dx.doi.org/10.5772/intechopen.73645…”
Section: Dvt Prophylaxis Guidelinesmentioning
confidence: 99%
“…It has also been reported that combination of this technique with CT venography provides higher sensitivity in detection PE [30]. In addition, it has been shown that transcranial Doppler ultrasonography technique which is based on detection DVT and high-intensity transient signals may screen patients for PE after orthopaedic surgery [31]. …”
Section: Diagnosis Of Vtementioning
confidence: 99%